2011
DOI: 10.1111/j.1365-2435.2011.01901.x
|View full text |Cite
|
Sign up to set email alerts
|

The penalty for arriving late in emerging salmonid juveniles: differences between species correspond to their interspecific competitive ability

Abstract: Summary1. Timing of offspring arrival (i.e. hatching, birth or emergence from nests) is commonly shown to have strong effects on their performance through body size and prior residency effects, but less is known about how such effects differ among species. The strength of such effects tends to be related to competitive intensity (e.g. population density). Variation in timing effects among species may therefore be expected to be related to their competitive ability. 2. Here, we test this hypothesis by conductin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…An important factor in the odds to establish and hold a territory is the timing of emergence, as early emerging alevins may have a competitive advantage owing to the prior residency effect (Hodge et al , ; Cutts et al , ; Kvingedal & Einum, ; Skoglund et al , ). In this study, hatching and emergence of farmed and wild S .…”
Section: Discussionmentioning
confidence: 99%
“…An important factor in the odds to establish and hold a territory is the timing of emergence, as early emerging alevins may have a competitive advantage owing to the prior residency effect (Hodge et al , ; Cutts et al , ; Kvingedal & Einum, ; Skoglund et al , ). In this study, hatching and emergence of farmed and wild S .…”
Section: Discussionmentioning
confidence: 99%
“…; Skoglund et al . ; Vehvilainen et al . ) or resistance to pathogens and other stressors (Jensen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Kennedy & Strange () reported similar results from streams in Northern Ireland, and Skoglund et al . () showed that juvenile S. trutta dominated similar sized S. salar in stream channels.…”
Section: Introductionmentioning
confidence: 99%